2010
DOI: 10.1177/0969733010369475
|View full text |Cite
|
Sign up to set email alerts
|

Courage and nursing practice: A theoretical analysis

Abstract: This article aims to deepen the understanding of courage through a theoretical analysis of classical philosophers' work and a review of published and unpublished empirical research on courage in nursing. The authors sought answers to questions regarding how courage is understood from a philosophical viewpoint and how it is expressed in nursing actions. Four aspects were identified as relevant to a deeper understanding of courage in nursing practice: courage as an ontological concept, a moral virtue, a property… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 18 publications
(48 reference statements)
0
52
0
11
Order By: Relevance
“…No primary research UK studies were found but there were three from outside the UK. Two of them were European (Swedish and Danish), namely Lindh et al (2010), who conducted a hermeneutical enquiry into moral strength, and Thorup et al (2012), whose interpretative study explored courage specific to vulnerability, suffering and ethics. The third paper, a hermeneutic research study exploring courage in practice, originated in New Zealand (Spence 2004) and suggests that courage in practice is essential.…”
Section: Concept Of Couragementioning
confidence: 99%
See 2 more Smart Citations
“…No primary research UK studies were found but there were three from outside the UK. Two of them were European (Swedish and Danish), namely Lindh et al (2010), who conducted a hermeneutical enquiry into moral strength, and Thorup et al (2012), whose interpretative study explored courage specific to vulnerability, suffering and ethics. The third paper, a hermeneutic research study exploring courage in practice, originated in New Zealand (Spence 2004) and suggests that courage in practice is essential.…”
Section: Concept Of Couragementioning
confidence: 99%
“…The review indicates that courage is seldom mentioned in nursing literature, which supports the observations of Spence (2004) and Murray (2010). Lindh et al (2010) state that, despite courage being identified as a fundamental component of nursing (Spence 2004, Cummings andBennett 2012), there is a lack of knowledge about nurses' courage in practice. Writers such as Gallagher (2010), Lachman (2010), LaSala and Bjarnason (2010), Lindh et al (2010) and Thorup et al (2012) identify factors that affect the development of courage.…”
Section: Concept Of Couragementioning
confidence: 99%
See 1 more Smart Citation
“…(Cummings and Bennett, 2012: 13) Courage has been recognised as a valuable human character trait since at least Aristotle's time . Aristotle considered courage to be a moral virtue; he defined courage as the ability to respond appropriately to fear (Lindh et al, 2010). Courage is important in nursing practice, for example, in relation to safeguarding people who are vulnerable, raising concerns about standards of care or challenging accepted practices, and to implement change.…”
Section: Couragementioning
confidence: 99%
“…Sellman (2011) argued that within today's healthcare system, where nurses must deliver safe and competent care within constrained resources, nurses need to be courageous and remain firm to their values. Lindh et al (2010) analysed courage and nursing practice and argued for the need to foster courage in nurses so they can act ethically and creatively, make changes, face challenges and motivate others through role modelling. In a different perspective of the need for courage, Thorup et al (2011) identified that nurses need the courage to help patients face their own suffering and vulnerability and to argue for and provide professional care.…”
Section: Couragementioning
confidence: 99%